Synergistic Cytotoxicity Effect by Combination of Methanol Extract of Parijoto Fruit (Medinilla speciosa Reinw. ex. Bl) and Cisplatin Against Hela Cell Line - Artanti, Anif Nur; Pujiastuti, Umi Hanik; Prihapsara, Fea; Rakhmawati, Rita (Indonesian Journal of Cancer Chemoprevention, 2020)
As one of the leading causes of death in worldwide, cervical cancer requires the effective therapies to reduce its mortality rate. One of the chemotherapy agents that frequently used in the treatment is cisplatin. However, due to drug resistance and its side effects, an agent that can be combined with cisplatin is needed. Parijoto fruit (Medinilla speciosa Reinw.ex.Bl) contains secondary metabolites compounds that have potential as anticancer. The study aims to determine the cytotoxic effect of methanol extract of Parijoto fruit calculated from the IC50 value and the synergicity of the combinational treatment with cisplatin evaluated from the Combination Index (CI) value and its cell viability by using MTT assay. Results showed that methanol extract of Parijoto fruit (MEP) performed cytotoxic effect on HeLa cell line with IC50 of 209.6 μg/mL while the value of IC50 of cisplatin against HeLa cells amounted to 12.8 μg/mL. The combination of 26.205 ppm (1/8 IC50) of MEP and 1.601 ppm (1/8 IC50) of Cisplatin performed synergistic effect on HeLa cell line with the CI value of 0.69. From the above results, it can be concluded that MEP is potential as co-chemotherapy agent based on the synergistic cytotoxicity effect with cisplatin.Keyword: cytotoxic, Medinilla speciosa, cisplatin, co-chemotherapy, MTT